Hydrophilic composition, hydrophilic film, article with hydrophilic film
A hydrophilic composition with specific inorganic particles and surface conditioners maintains hydrophilicity on materials exposed to high temperatures, addressing the issue of heat-induced hydrophilicity loss in existing films.
Patent Information
- Application Number
- JP2023094786
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-19
AI Technical Summary
Existing hydrophilic films on materials like glass, polycarbonate, and metal surfaces lose hydrophilicity when exposed to high temperatures, such as those encountered in windshields and headlamps, necessitating a composition that maintains hydrophilicity under heat.
A hydrophilic composition containing inorganic particles, such as silica and alumina, and a surface conditioning agent with an HLB value of 12 to 19, including compounds like polyglycerin fatty acid esters and acetylene glycols, is applied to form a film that retains hydrophilicity even at elevated temperatures.
The composition provides excellent heat resistance and maintains hydrophilicity on treated surfaces, preventing fogging and ensuring effective water film formation even under high-temperature conditions.
Smart Images

Figure 2024176326000001 
Figure 2024176326000002 
Figure 2024176326000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a hydrophilic composition, a hydrophilic film, and an article with a hydrophilic film. [Background technology]
[0002] By making a material hydrophilic, various useful effects can be obtained. For example, when the surfaces of glass, lenses, mirrors, etc. are made hydrophilic, water droplets that adhere to the surface spread out and form a uniform water film, making the surface less likely to fog up.
[0003] As a technique for making a member hydrophilic, a method has been proposed in which a hydrophilic composition is applied onto the member to provide a hydrophilic film (for example, Patent Document 1 listed below). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2023-030386 A Summary of the Invention [Problem to be solved by the invention]
[0005] Glass, polycarbonate, metal, fiber, and other materials used in windshields, building glass, sensor lenses, headlamps, solar panels, electric wires, outdoor tents, etc., are sometimes exposed to high-temperature environments for long periods of time. Therefore, the hydrophilic film formed on these materials is required to have heat resistance that makes it difficult for the hydrophilicity to decrease due to heat. In particular, the surface temperature of windshields can reach 100°C, and the inside of headlamps can reach about 100°C due to heat from the headlight bulb, so in heat resistance tests for hydrophilic films, it is necessary to maintain a specified level of hydrophilicity for a longer period of time than before under high-temperature conditions such as 130°C.
[0006] In view of the above, an object of the present disclosure is to provide a hydrophilic composition that can impart hydrophilicity to a desired member and has excellent heat resistance. Another object of the present disclosure is to provide a hydrophilic film and an article with a hydrophilic film. [Means for solving the problem]
[0007] In order to solve the above problems, the present disclosure provides the following hydrophilic composition, hydrophilic film, and article with a hydrophilic film.
[0008] [1] A hydrophilic composition comprising inorganic particles and a surface conditioner, the surface conditioner including a compound having a hydroxyl group, the compound having an HLB value of 12 or more and 19 or less. [2] The hydrophilic composition according to [1], wherein the compound is a polyglycerin fatty acid ester compound. [3] The hydrophilic composition according to [2], wherein the polyglycerol fatty acid ester compound is a compound represented by the following general formula (1): [ka] [In formula (1), a represents an integer of 1 or more, and R 1 represents a hydrocarbon group having 10 or more carbon atoms. [4] The hydrophilic composition according to [1], wherein the compound is an acetylene glycol compound. [5] The hydrophilic composition according to [4], wherein the acetylene glycol compound is a compound represented by the following general formula (2): [ka] [In formula (2), m and n are each independently an integer of 0 or more, and m+n is 1 or more; R 2 , R 3 , R 4 , and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; L 1 , L 2 each independently represents an ethylene group or a propylene group. [6] A hydrophilic film comprising inorganic particles and a surface conditioner, the surface conditioner including a compound having a hydroxyl group, the compound having an HLB value of 12 or more and 19 or less. [7] The hydrophilic film described in [6], wherein the compound is a polyglycerin fatty acid ester compound. [8] The hydrophilic film according to [7], wherein the polyglycerol fatty acid ester compound is a compound represented by the following general formula (1): [ka] [In formula (1), a represents an integer of 1 or more, and R 1 represents a hydrocarbon group having 10 or more carbon atoms. [9] The hydrophilic film described in [6], wherein the compound is an acetylene glycol compound.
[10] The hydrophilic film according to [9], wherein the acetylene glycol compound is a compound represented by the following general formula (2): [ka] [In formula (2), m and n are each independently an integer of 0 or more, and m+n is 1 or more; R 2 , R 3 , R 4 , and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; L 1 , L 2 each independently represents an ethylene group or a propylene group.
[11] An article with a hydrophilic film, comprising the hydrophilic film according to any one of [6] to
[10] . Effect of the Invention
[0009] According to the present disclosure, it is possible to provide a hydrophilic composition that can impart hydrophilicity to a desired member and has excellent heat resistance. In addition, the present disclosure can provide a hydrophilic film and an article with a hydrophilic film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the present specification, a numerical range indicated using "to" includes the numerical values before and after "to" as the minimum and maximum values, respectively. In addition, in a numerical range described in stages in this specification, an upper limit or lower limit value described in one numerical range may be replaced with an upper limit or lower limit value of another numerical range described in stages. In addition, in a numerical range described in this specification, an upper limit or lower limit value of the numerical range may be replaced with a value shown in an example.
[0011] <Hydrophilic composition> The hydrophilic composition of the present embodiment contains inorganic particles and a surface conditioner.
[0012] (Inorganic particles) Examples of inorganic particles include metal oxide fine particles such as silica particles, alumina particles, zirconia particles, titania particles, zinc oxide particles, and ceria particles. These may be used alone or in combination of two or more. The inorganic particles may be colloidal particles such as alumina sol, colloidal silica, silica sol, zirconia sol, titania sol, zinc oxide sol, and ceria sol. The colloidal particles may be an acidic sol, an alkaline sol, or a sol stabilized in the neutral range.
[0013] The inorganic particles may have a polar group, such as a hydroxyl group, an amino group, a sulfo group or an aluminol group, on the surface.
[0014] The inorganic particles may have an average particle size of 1 to 200 nm, or 2 to 50 nm, as measured by dynamic light scattering.
[0015] The content of the inorganic particles may be 0.01 to 5.0 mass%, 0.1 to 2.0 mass%, 0.3 to 1.5 mass%, or 0.5 to 1.0 mass%, based on the total amount of the composition.
[0016] The hydrophilic composition of the present embodiment may contain silica particles from the viewpoints of transparency, hydrophilicity, and versatility.
[0017] The particle size of the silica particles may be an average particle size of 3 to 700 nm or 5 to 500 nm measured by a dynamic light scattering method, and may be 20 nm or less or 10 nm or less from the viewpoint of transparency or preventing the occurrence of interference fringes.
[0018] The shape of the silica particles is not particularly limited, and may be a rosary (pearl necklace), a chain, a sphere, a cocoon, an association, or a confetti. Among these, from the viewpoint of forming a good (uniform) water film when moisture is attached, a sphere, a rosary (pearl necklace) and a chain are preferred. The uniformity of the water film can be evaluated, for example, by the method described in WO2022 / 107823.
[0019] The silica particles may contain a metal oxide other than silicon dioxide. The type of metal oxide is not particularly limited, but may be, for example, alumina. Such silica particles may be colloidal silica formed by polycondensation reaction of aluminosilicate in an amount sufficient for stabilizing silica sol with silanol groups on the surface of colloidal silica. The silica particles may be modified with alumina alkoxide in order to form a good (uniform) water film when moisture is attached and to easily ensure surface hardness.
[0020] The silica particles may be colloidal silica. The colloidal silica may have an average particle diameter (secondary particle diameter) of 1 to 1000 nm. When the average particle diameter is 1 nm or more, the particles are less likely to aggregate in the hydrophilic composition, and the particles are more likely to adhere to the member. On the other hand, when the average particle diameter is 1000 nm or less, the specific surface area of the particles is increased, and the particles are more likely to adhere to the member. From this viewpoint, the average particle diameter of the colloidal silica may be 3 to 700 nm, or 5 to 500 nm.
[0021] The average particle size can be measured, for example, by the following procedure. First, about 100 μL (L stands for liters; the same applies below) of the colloidal silica dispersion is weighed out and diluted with ion-exchanged water to obtain a dilute solution so that the colloidal silica content is about 0.05% by mass (content at which the transmittance (H) during measurement is 60 to 70%). The dilute solution is then placed in the sample tank of a laser diffraction particle size distribution analyzer (manufactured by Horiba, Ltd., product name: LA-920, refractive index: 1.93, light source: He-Ne laser, absorption 0), and the average particle size can be measured.
[0022] The number of silanol groups per gram of colloidal silica is 10 x 10 18 ~1000×10 18 50×10 18 ~800×10 18 pcs / g or 100×10 18 ~700×10 18 The number of silanol groups per 1 g of colloidal silica may be 10×10 18 By having a silanol group density of 1000×10 or more per gram, the number of chemical bonding points with the functional groups of the component increases, which makes it easier to improve adhesion to the component. 18 By keeping the content at or less than 1 / g, a sudden polycondensation reaction between colloidal silica particles during preparation of the anti-fogging liquid can be suppressed, and a decrease in the number of chemical bonding points with functional groups of the component can be suppressed.
[0023] In this embodiment, the number of silanol groups (ρ [groups / g]) can be measured and calculated by titration as follows.
[0024] [1] First, weigh out 15 g of colloidal silica into a container (X [g]) whose mass has been measured, and disperse it in an appropriate amount of water (100 ml or less). If the colloidal silica is in the form of a dispersion liquid dispersed in a medium such as water, measure out the dispersion liquid into the container so that the amount of colloidal silica is 15 g.
[0025] [2] Next, adjust the pH to 3.0-3.5 with 0.1 mol / L hydrochloric acid, measure the mass (Y [g]) at this point, and calculate the total mass of the liquid (YX [g]).
[0026] [3] Weigh out 1 / 10 of the mass obtained in [2] above ((YX) / 10[g]) of the liquid into a separate container. At this stage, the colloidal silica (A[g]) contained in the liquid is 1.5g.
[0027] [4] Add 30 g of sodium chloride and then ultrapure water to make the total amount 150 g. Adjust the pH to 4.0 with 0.1 mol / L sodium hydroxide solution to prepare the titration sample.
[0028] [5] Add 0.1 mol / L sodium hydroxide to the titration sample until the pH reaches 9.0, and calculate the amount of sodium hydroxide (B [mol]) required to change the pH from 4.0 to 9.0.
[0029] [6] Calculate the number of silanol groups in the colloidal silica using the following formula (A). ρ = B NA / A SBET (A) (In formula (A), NA [mol / mol] represents Avogadro's number. SBET [m 2 / g] indicates the BET specific surface area of colloidal silica.)
[0030] The BET specific surface area SBET is determined according to the BET specific surface area method. As a specific measurement method, for example, colloidal silica is placed in a dryer, dried at 150°C, and then placed in a measurement cell and vacuum degassed for 60 minutes at 120°C. The sample is then measured by a single-point method or a multi-point method in which nitrogen gas is adsorbed using a BET specific surface area measurement device. More specifically, the colloidal silica dried at 150°C is first crushed finely in a mortar (porcelain, 100 ml) and placed in a measurement cell as a measurement sample, and the BET specific surface area SBET is measured using a BET specific surface area measurement device (product name NOVE-1200) manufactured by Yuasa Ionics Co., Ltd.
[0031] The degree of association of colloidal silica may be, for example, 5.0 or less, 4.0 or less, 3.0 or less, 2.5 or less, or 2.0 or less. When the degree of association is in this range, the specific surface area of colloidal silica is appropriately increased, thereby improving adhesion to a member. In addition, colloidal silica having such a degree of association is easy to obtain. The degree of association may be 1.0 or more, 1.3 or more, or 1.5 or more. When the degree of association is in this range, the specific surface area of colloidal silica is appropriately decreased, thereby suppressing aggregation of colloidal silica during preparation of a hydrophilic composition.
[0032] Here, in this specification, the degree of association of colloidal silica in a colloidal silica dispersion refers to the ratio of the average particle size of the secondary particles of colloidal silica in the dispersion to the biaxial average primary particle size of colloidal silica (average particle size of secondary particles / biaxial average primary particle size). The average primary particle size can be measured, for example, by a known transmission electron microscope (for example, H-7100FA, product name, manufactured by Hitachi High-Tech Corporation). For example, an image of particles is taken using an electron microscope, and the biaxial average primary particle size is calculated for a predetermined number of arbitrary particles, and the average value of these is obtained. In the case of colloidal silica, the particle size is generally uniform, so the number of particles to be measured may be, for example, about 20 particles. The average particle size of secondary particles refers to the value obtained by the above-mentioned method.
[0033] The content of colloidal silica can be 0.01 to 5.0% by mass based on the total amount of the composition. When the content is 0.01% by mass or more, sufficient antifogging properties are easily exhibited, while when the content is 5.0% by mass or less, the polycondensation reaction of silanol groups between particles is suppressed, and antifogging properties (hydrophilicity) are easily maintained. From this viewpoint, the content of colloidal silica may be 0.1 to 2.0% by mass, 0.3 to 1.5% by mass, or 0.5 to 1.0% by mass.
[0034] Colloidal silica is available as a colloidal silica dispersion. Examples of the dispersion medium include water, isopropyl alcohol, 1-methoxy-2-propyl alcohol, ethyl alcohol, methyl alcohol, ethylene glycol, ethylene glycol-n-propyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, dimethylacetamide, N-methylpyrrolidone, toluene, methyl ethyl ketone, methyl isobutyl ketone, cyclohexane, and ethyl acetate. The dispersion medium may be water, alcohols, or a mixture of water and alcohols. Among these, water is preferred from the viewpoint of versatility.
[0035] The pH of the colloidal silica dispersion may be 2 to 10. By setting the pH to 6 to 8, when an alkoxy group is present on the surface of the colloidal silica, the hydrolysis reaction rate is slowed down. This makes it easy to form the colloidal silica with the remaining alkoxy group into a coating film. In this case, the polycondensation reaction of the silanol group due to moisture absorption can be suppressed, so that the anti-fogging property (hydrophilicity) of the film surface can be easily maintained. By setting the pH to 2 to 5 or 8 to 10, when an alkoxy group is present on the surface of the colloidal silica, the hydrolysis reaction rate is increased. This makes it possible to generate more silanol groups, and the adhesion to the member can be easily improved.
[0036] The pH of the colloidal silica dispersion can be measured with a pH meter (e.g., model number PHL-40, manufactured by Denki Kagaku Keiki Co., Ltd.). The measured pH is measured by three-point calibration using standard buffer solutions (phthalate pH buffer solution, pH: 4.01 (25°C), neutral phosphate pH buffer solution, pH: 6.86 (25°C), borate pH buffer solution, pH: 9.18 (25°C)), after which the electrode is placed in the dispersion and the value obtained after 2 minutes or more have elapsed and the solution has stabilized.
[0037] The zeta potential of the colloidal silica in the dispersion is preferably -50mV to 40mV. When the zeta potential is -10mV to 10mV, the particles are less likely to repel each other when coated, and the particles are closely attached to the member, which makes it easier to improve the hydrophilicity of the member. When the zeta potential is -50mV to -11mV or 11mV to 40mV, the particles are more likely to repel each other in the dispersion, which makes it easier to suppress particle aggregation because the dispersibility is increased.
[0038] The zeta potential of colloidal silica can be measured with a zeta potential meter (e.g., Beckman Coulter, model number: Coulter Delsa 440). The zeta potential is measured by first adding pure water to a colloidal silica dispersion so that the silica particle concentration is 5 ppm based on the total volume of the test solution, and then dispersing the silica particles by ultrasonic treatment to prepare a test solution. Next, the test solution is placed in a measurement cell with platinum electrodes on both sides, and a voltage of 10 V is applied to both electrodes. The charged silica particles move to the electrode with the opposite polarity to their charge. The migration speed of these charged silica particles is then calculated.
[0039] When the hydrophilic composition of the present embodiment contains silica particles and the pH of the liquid is weakly acidic to neutral, the zeta potential of the silica particles (for example, the above-mentioned colloidal silica) may be negative.
[0040] The raw material for colloidal silica is not particularly limited and may be water glass or alkoxysilane.
[0041] The preparation process when the raw material is water glass is not particularly limited, but for example, sodium silicate is heated and concentrated by hydrothermal synthesis to prepare particles. For example, agglomerates with a three-dimensional network structure may be prepared in a state where the growth of primary particles is suppressed at an acidic pH and then disintegrated, or a block-shaped aggregate may be prepared by accelerating the growth of primary particles at an alkaline pH and then disintegrated.
[0042] The preparation process when the raw material is alkoxysilane is not particularly limited, but for example, alkoxysilane is subjected to sol-gel synthesis to prepare particles. For example, after accelerating the hydrolysis reaction of alkoxysilane, a polycondensation reaction may be accelerated to obtain a gel, and then the internal solvent may be removed by heat treatment. Alternatively, after obtaining the gel, the solvent may be replaced with a predetermined solvent.
[0043] As the colloidal silica dispersion, a commercially available product may be used, for example, ST-PS-SO (manufactured by Nissan Chemical Industries, Ltd.), ST-PS-MO (manufactured by Nissan Chemical Industries, Ltd.), ST-PS-M (manufactured by Nissan Chemical Industries, Ltd.), ST-PS-S (manufactured by Nissan Chemical Industries, Ltd.), ST-UP (manufactured by Nissan Chemical Industries, Ltd.), ST-OUP (manufactured by Nissan Chemical Industries, Ltd.), IPA-ST-UP (manufactured by Nissan Chemical Industries, Ltd.), MA-ST-UP (manufactured by Nissan Chemical Industries, Ltd.), PGM-ST-UP (manufactured by Nissan Chemical Industries, Ltd.), MEK-ST-UP (manufactured by Nissan Chemical Industries, Ltd.), IPA-ST (manufactured by Nissan Chemical Industries, Ltd.), IPA- ST-L (Nissan Chemical Co., Ltd.), IPA-ST-ZL (Nissan Chemical Co., Ltd.), MA-ST-M (Nissan Chemical Co., Ltd.), MA-ST-L (Nissan Chemical Co., Ltd.), MA-ST-ZL (Nissan Chemical Co., Ltd.), EG-ST (Nissan Chemical Co., Ltd.), EG-ST-XL-30 (Nissan Chemical Co., Ltd.), NPC-ST-30 (Nissan Chemical Co., Ltd.), PGM-ST (Nissan Chemical Co., Ltd.), DMAC-ST (Nissan Chemical Co., Ltd.), DMAC-ST-ZL (Nissan Chemical Co., Ltd.), NMP-ST (Nissan Chemical Co., Ltd.), TOL-ST (Nissan Chemical Co., Ltd.) (Nissan Chemical Co., Ltd.), MEK-ST-40 (Nissan Chemical Co., Ltd.), MEK-ST-L (Nissan Chemical Co., Ltd.), MEK-ST-ZL (Nissan Chemical Co., Ltd.), MIBK-ST (Nissan Chemical Co., Ltd.), MIBK-ST-L (Nissan Chemical Co., Ltd.), CHO-ST-M (Nissan Chemical Co., Ltd.), EAC-ST (Nissan Chemical Co., Ltd.), PMA-ST (Nissan Chemical Co., Ltd.), MEK-EC-2130Y (Nissan Chemical Co., Ltd.), MEK-EC-2430Z (Nissan Chemical Co., Ltd.), MEK-EC-2140Z (Nissan Chemical Co., Ltd.), MEK-AC-4130Z (Nissan Chemical Co., Ltd.) (Nissan Chemical Co., Ltd.), MEK-AC-5140Z (Nissan Chemical Co., Ltd.), PGM-AC-2140Y (Nissan Chemical Co., Ltd.), PGM-AC-4130Y (Nissan Chemical Co., Ltd.), MIBK-AC-2140Z (Nissan Chemical Co., Ltd.), MIBK-SD-L (Nissan Chemical Co., Ltd.), ST-XS (Nissan Chemical Co., Ltd.), ST-OXS (Nissan Chemical Co., Ltd.), ST-NXS (Nissan Chemical Co., Ltd.), ST-CXS (Nissan Chemical Co., Ltd.), ST-S (Nissan Chemical Co., Ltd.), ST-OS (Nissan Chemical Co., Ltd.), ST-NS (Nissan Chemical Co., Ltd.),ST-30 (manufactured by Nissan Chemical Co., Ltd.), ST-O (manufactured by Nissan Chemical Co., Ltd.), ST-N (manufactured by Nissan Chemical Co., Ltd.), ST-C (manufactured by Nissan Chemical Co., Ltd.), ST-AK (manufactured by Nissan Chemical Co., Ltd.), ST-50-T (manufactured by Nissan Chemical Co., Ltd.), ST-O-40 (manufactured by Nissan Chemical Co., Ltd.), ST-N-40 (manufactured by Nissan Chemical Co., Ltd.), ST-CM (manufactured by Nissan Chemical Co., Ltd.), ST-30L (manufactured by Nissan Chemical Co., Ltd.), ST-OL (manufactured by Nissan Chemical Co., Ltd.), ST-AK-L (manufactured by Nissan Chemical Co., Ltd.), ST-YL (Manufactured by Nissan Chemical Co., Ltd.), ST-OYL (Manufactured by Nissan Chemical Co., Ltd.), ST-AK-YL (Manufactured by Nissan Chemical Co., Ltd.), ST-ZL (Manufactured by Nissan Chemical Co., Ltd.), MP-1040 (Manufactured by Nissan Chemical Co., Ltd.), MP-2040 (Manufactured by Nissan Chemical Co., Ltd.), MP-4540M (Manufactured by Nissan Chemical Co., Ltd.), PL-1-IPA (Manufactured by Fuso Chemical Co., Ltd.), PL-1-TOL (Manufactured by Fuso Chemical Co., Ltd.), PL-2L-PGME (Manufactured by Fuso Chemical Co., Ltd.), PL-2L-MEK (Manufactured by Fuso Chemical Co., Ltd.), PL-2L (Manufactured by Fuso Chemical Co., Ltd.) (manufactured by Fuso Chemical Co., Ltd.), PL-3 (manufactured by Fuso Chemical Co., Ltd.), PL-4 (manufactured by Fuso Chemical Co., Ltd.), PL-5 (manufactured by Fuso Chemical Co., Ltd.), PL-1H (manufactured by Fuso Chemical Co., Ltd.), PL-3H (manufactured by Fuso Chemical Co., Ltd.), PL-5H (manufactured by Fuso Chemical Co., Ltd.), BS-2L (manufactured by Fuso Chemical Co., Ltd.), BS-3L (manufactured by Fuso Chemical Co., Ltd.), BS-5L (manufactured by Fuso Chemical Co., Ltd.), HL-2L (manufactured by Fuso Chemical Co., Ltd.), HL-3L (manufactured by Fuso Chemical Co., Ltd.), HL-4L (manufactured by Fuso Chemical Co., Ltd.), PL-3-C (manufactured by Fuso Chemical Co., Ltd.), PL-3-D (manufactured by Fuso Chemical Co., Ltd.), TCSOL800 (manufactured by Tama Chemical Industry Co., Ltd.), SI-40 (manufactured by JGC Catalysts and Chemicals Co., Ltd.), SI-50 (manufactured by JGC Catalysts and Chemicals Co., Ltd.), SI-45P (manufactured by JGC Catalysts and Chemicals Co., Ltd.), SI-80P (manufactured by JGC Catalysts and Chemicals Co., Ltd.), SIK-23 (manufactured by JGC Catalysts and Chemicals Co., Ltd.), S-30H (manufactured by JGC Catalysts and Chemicals Co., Ltd.), SIK-15 (manufactured by JGC Catalysts and Chemicals Co., Ltd.), and SI-550 (manufactured by JGC Catalysts and Chemicals Co., Ltd.).
[0044] The content of the silica particles may be 0.01 to 5.0 mass%, 0.1 to 2.0 mass%, 0.3 to 1.5 mass%, or 0.5 to 1.0 mass%, based on the total amount of the composition.
[0045] The hydrophilic composition of the present embodiment may contain alumina particles from the viewpoints of transparency and scratch resistance.
[0046] The alumina particles may have an average particle size of 1 to 500 nm or 5 to 100 nm as measured by dynamic light scattering. The average particle size of the alumina particles may be 50 nm or less or 20 nm or less from the viewpoint of transparency or preventing the occurrence of interference fringes.
[0047] The shape of the alumina particles may be granular, feathery, spherical, needle-like, or rod-like. Among these, from the viewpoint of transparency or from the viewpoint of preventing the occurrence of interference fringes, the alumina particles may be granular, or may have an aspect ratio of 10 or less. Here, the aspect ratio is a value calculated by dividing the major axis L of the alumina particles by the minor axis S (major axis L / minor axis S).
[0048] The alumina particles may be in the form of an alumina sol, which is a colloidal solution in which alumina hydrate particles are dispersed in a dispersion medium.
[0049] As the alumina sol, commercially available products may be used, for example, AS-520-A (manufactured by Nissan Chemical Industries, Ltd.), AS-200 (manufactured by Nissan Chemical Industries, Ltd.), Aluminasol F-3000 (manufactured by Kawaken Fine Chemicals), Aluminasol-10A (manufactured by Kawaken Fine Chemicals), Aluminasol CSA-110AD (manufactured by Kawaken Fine Chemicals), Aluminasol-10D (manufactured by Kawaken Fine Chemicals), Aluminasol-A2 (manufactured by Kawaken Fine Chemicals), Examples of such alumina sol include Alumina Sol-F1000 (manufactured by Kawaken Fine Chemicals), Alumina Sol CSA-30AD (manufactured by Kawaken Fine Chemicals), Organo Alumina Sol (manufactured by Kawaken Fine Chemicals), Clear Sol (manufactured by Kawaken Fine Chemicals), AL-7 (manufactured by Taki Chemicals), AL-ML15 (manufactured by Taki Chemicals), AL-C20 (manufactured by Taki Chemicals), AS-L10 (manufactured by Taki Chemicals), and Cataloid Series (specialty products) (manufactured by JGC Catalysts and Chemicals).
[0050] The content of the alumina particles may be 0.01 to 5.0 mass%, 0.1 to 2.0 mass%, 0.3 to 1.5 mass%, or 0.5 to 1.0 mass%, based on the total amount of the composition.
[0051] (Surface conditioner) The surface conditioner includes a compound having a hydroxyl group. From the viewpoint of forming a hydrophilic film having excellent heat resistance, the HLB value of the compound having a hydroxyl group is 12 or more and 19 or less.
[0052] "HLB (Hydrophilic-Lipophilic Balance) value" is a value that represents the balance between hydrophilicity and lipophilicity of a compound. The HLB value can be determined by calculation even when the type of hydrophobic group, the type of hydrophilic group, or the copolymerization ratio, etc., are different in one compound.
[0053] Several methods for calculating the HLB value have been proposed. For example, the HLB value is calculated by the Griffin method represented by the following formula. The HLB value is a value between 0 and 20.0. The closer the HLB value is to 0, the higher the lipophilicity, and the closer the HLB value is to 20.0, the higher the hydrophilicity. HLB value = 20 x (total molecular weight of hydrophilic group portion) / (total molecular weight)
[0054] The hydrophilic composition of the present embodiment contains inorganic particles and a compound having a hydroxyl group with an HLB value of 12 to 19, and thus can form a hydrophilic film having excellent heat resistance on a member. The present inventors speculate as follows as to the reason why such an effect is obtained. First, it is considered that the compound having a hydroxyl group and the inorganic particles can be sufficiently uniformly dispersed in the composition by interacting with each other. Therefore, it is considered that when the composition is made into a film, the aggregation of the compound having a hydroxyl group is suppressed, and the compound having a hydroxyl group can be sufficiently interposed between the inorganic particles. In addition, since the compound having a hydroxyl group in the hydrophilic film composed of inorganic particles is sufficiently dispersed, it is speculated that the aggregation of the compound having a hydroxyl group is unlikely to occur even when the hydrophilic film is heated, and the deterioration of hydrophilicity due to heating is unlikely to occur.
[0055] The HLB value of the compound having a hydroxyl group may be 12.5 or more, 13 or more, or 14 or more from the viewpoint of solubility, and may be 18.5 or less, 18 or less, 17 or less, 16 or less, or 15.5 or less from the viewpoint of water resistance.
[0056] The compound having a hydroxyl group may be a fatty acid ester compound or an acetylene glycol compound.
[0057] The fatty acid ester compound may be a polyglycerol fatty acid ester compound. The polyglycerol fatty acid ester compound may be a compound represented by the following general formula (1). [ka] In formula (1), a represents an integer of 1 or more, R 1 represents a hydrocarbon group having 10 or more carbon atoms.
[0058] In the above formula (1), R 1 may be a hydrocarbon group having from 11 to 22 carbon atoms, or may be a hydrocarbon group having from 11 to 15 carbon atoms. The hydrocarbon group may be a chain saturated hydrocarbon group.
[0059] The compound represented by the above formula (1) can be obtained by esterification reaction between polyglycerol and fatty acid. Examples of fatty acid include myristic acid, palmitic acid, stearic acid, behenic acid, etc. The esterification reaction between polyglycerol and fatty acid can be carried out by a conventionally known method.
[0060] The compound represented by the above formula (1) may be a commercially available product, such as L-7D (manufactured by Mitsubishi Chemical Corporation, trade name, HLB value: 17, polyglycerol laurate), M-7D (manufactured by Mitsubishi Chemical Corporation, trade name, HLB value: 16, polyglycerol myristate), etc.
[0061] Examples of the acetylene glycol compound include acetylene glycol and alkylene oxide adducts of acetylene glycol.
[0062] The acetylene glycol compound may be a compound represented by the following general formula (2).
[0063] [ka] In formula (2), m and n are each independently an integer of 0 or more, and m+n is 1 or more. 2 , R 3 , R 4 , and R 5 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. 1 , L 2 each independently represents an ethylene group or a propylene group.
[0064] In the above formula (2), when m is 2 or more, a plurality of -OL 1 - may be the same or different. When n is 2 or more, a plurality of -OL 2 - may be the same or different. 1 -OR-OL2 The structural units represented by - may be present randomly or may form blocks, where m and n represent the number of each structural unit.
[0065] In the above formula (2), R 2 , R 3 , R 4 , and R 5 may each independently be a hydrogen atom, a methyl group, an ethyl group, a propyl group, or a butyl group.
[0066] The compound represented by the above formula (2) can be obtained by converting acetylene glycol represented by the following general formula (3) into an alkylene oxide. The conversion of acetylene glycol into an alkylene oxide can be performed by a conventionally known method.
[0067] [ka] In formula (3), R 6 , R 7 , R 8 , R 9 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0068] Examples of the acetylene glycol represented by the above formula (3) include 5,8-dimethyl-6-dodecyne-5,8-diol, 4,7-dimethyl-5-decyne-4,7-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 2,3,6,7-tetramethyl-4-octyne-3,6-diol, 3,6-dimethyl-4-octyne-3,6-diol, 3,6-diethyl-4-octyne-3,6-diol, and 2,5-dimethyl-3-hexyne-2,5-diol.
[0069] The compound represented by the above formula (2) may be a commercially available product, for example, Surfynol 465 (trade name, manufactured by Nissin Chemical Industry Co., Ltd., HLB value: 13, acetylene glycol compound).
[0070] The heat resistant temperature of the surface conditioner may be 130° C. or higher and 200° C. or lower, from the viewpoint of providing a composition with better heat resistance. The heat resistant temperature is defined as the temperature at which the weight of the surface conditioner is reduced by 1% when the weight reduction of the surface conditioner is measured using a simultaneous thermogravimetry and differential thermal analyzer (e.g., TG-DTA6300 (manufactured by Hitachi High-Tech Science Corporation)).
[0071] From the viewpoints of anti-fogging properties, heat resistance, and scratch resistance, the content of the surface conditioner may be 30 to 300 parts by mass, 40 to 250 parts by mass, or 50 to 200 parts by mass relative to 100 parts by mass of the inorganic particles.
[0072] Furthermore, from the viewpoint of adhesion to members, the content of the surface conditioner may be 0.01 to 3.0 mass %, 0.1 to 2.0 mass %, or 0.3 to 1.0 mass %, based on the total amount of the composition.
[0073] From the viewpoints of anti-fogging property, heat resistance, and scratch resistance, the hydrophilic composition of the present embodiment may have a surface conditioner content of 1.5 to 30 parts by mass, or 3.0 to 20 parts by mass, relative to 100 parts by mass of inorganic particles (particularly alumina particles).
[0074] The hydrophilic composition of the present embodiment may contain a liquid medium from the viewpoint of dispersibility and coatability. The liquid medium is a medium that disperses inorganic particles in the composition, dissolves a surface conditioner, and the like. The liquid medium may be a medium having a boiling point lower than 185° C. The liquid medium volatilizes when the coating film is heated, which causes the inorganic particles to approach each other and facilitates the formation of bonds.
[0075] As the liquid medium, for example, water, an organic solvent, or a mixture thereof can be used. Examples of the organic solvent include alcohols such as methyl alcohol, ethyl alcohol, 1-propanol, isopropyl alcohol, 1-butyl alcohol, 2-butyl alcohol, isobutyl alcohol, diacetone alcohol, 1-butoxy-2-propanol, 1-hexanol, 1-octanol, 2-octanol, and 3-methoxy-3-methyl-1-butanol, glycols such as polyethylene glycol, glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol mono-tert-butyl ether, propylene glycol monomethyl ether acetate, propylene glycol n-propyl ether, and propylene glycol monomethyl ether, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran and dioxane, esters such as ethyl acetate and butyl acetate, cyclic hydrocarbons such as cyclohexane, and acetonitrile. These may be used alone or in a mixture of two or more.
[0076] In the hydrophilic composition of the present embodiment, from the viewpoint of environmental friendliness, the liquid medium may be one or more of water, ethyl alcohol, 1-propanol, isopropyl alcohol, 1-butyl alcohol, 2-butyl alcohol, and isobutyl alcohol.
[0077] The hydrophilic composition of the present embodiment may have a non-volatile content of 0.05 to 10 mass%, 0.1 to 8.5 mass%, or 0.5 to 7 mass%. The non-volatile content refers to a value calculated by Ma×100 / Mb, where Ma is the mass of the composition when heated at 100° C. for 60 minutes, and Mb is the mass of the composition before heating.
[0078] The hydrophilic composition of the present embodiment may contain various additives, such as a catalyst, an antioxidant, an ultraviolet absorber, a light stabilizer, a thickener, an anti-condensation agent, an anti-snow agent, and an anti-fouling agent, as necessary, within a range in which the desired effects can be obtained.
[0079] Examples of the catalyst include acetic acid, nitric acid, hydrochloric acid, nitric acid, phosphoric acid, sulfate, paratoluenesulfonic acid, benzenesulfonic acid, methanesulfonic acid, phenolsulfonic acid, oxalic acid, maleic acid, malonic acid, tartaric acid, citric acid, malic acid, acetic acid, lactic acid, succinic acid, benzoic acid, ammonia, urea, imidazole, sodium carbonate, calcium carbonate, and sodium acetate.
[0080] The hydrophilic composition of the present embodiment may be a non-surfactant type. The term "non-surfactant type" means that the surfactant content is 1% by mass or less based on the total amount of non-volatile matter in the composition, or that the composition does not contain any surfactant. The surfactant may be an anionic surfactant, a cationic surfactant, a nonionic surfactant, an amphoteric surfactant, or the like.
[0081] According to the hydrophilic composition of the present embodiment, it is possible to impart hydrophilicity to a desired member. For example, a hydrophilic film can be formed by applying the hydrophilic composition to a desired member and drying it. The hydrophilic composition of the present embodiment may also be applied to a dew condensation prevention agent, a snow adhesion prevention agent, or an antifouling agent.
[0082] Examples of the members include glass substrates, polycarbonate substrates, acrylic substrates, etc. Examples of the members include automotive members such as glass inner surfaces, interior antennas, heater films, side mirrors, and sensor lenses, optical members such as display lenses, traffic lights, and warning lights, electrical appliances such as commercial freezer doors, architectural members such as glass windows, bathrooms, and shower mirrors, sports visors, glasses, masks, and food packaging materials.
[0083] Examples of the coating method include spin coating, dip coating, spray coating, flow coating, bar coating, gravure coating, bar coating, and wiping. In particular, spray coating is preferred from the viewpoint of easily forming a hydrophilic film of uniform thickness even on uneven surfaces to be treated, high productivity, and high use efficiency of the hydrophilic composition. These methods may be used alone or in combination of two or more. The hydrophilic composition may be applied by soaking it into a cloth or the like.
[0084] The drying temperature may be, for example, 5 to 100° C., or may be 10 to 80° C. The drying time may be, for example, 60 seconds to 5 hours.
[0085] <Hydrophilic membrane> The hydrophilic film of the present embodiment contains inorganic particles and a surface conditioner. The inorganic particles and the surface conditioner and the content ratio thereof may be the same as those in the hydrophilic composition described above. The hydrophilic film of the present embodiment may also contain the various additives described above.
[0086] The hydrophilic film of the present embodiment can be formed by applying the above-mentioned hydrophilic composition of the present embodiment under the above-mentioned conditions and drying it.
[0087] The thickness of the hydrophilic film may be 1 nm to 1000 μm, 10 nm to 500 μm, or 100 nm to 2 μm from the viewpoints of transparency, anti-fogging properties, scratch resistance, etc. The thickness of the hydrophilic film may be measured, for example, by a non-contact film thickness gauge, Optical NanoGauge C13027 (manufactured by Hamamatsu Photonics K.K.).
[0088] <Items with hydrophilic film>
[0089] The hydrophilic film-attached article of the present embodiment includes an article and the hydrophilic film of the present embodiment provided on the article.
[0090] The article may be any of the members described above. EXAMPLES
[0091] The present disclosure will be described in more detail below with reference to examples, although the present disclosure is not limited to these examples.
[0092] <Preparation of Hydrophilic Composition> Example 1 0.5 g of AS-520-A (Nissan Chemical Industries, Ltd., product name, non-volatile content concentration 20% by mass), which is a colloidal solution of alumina hydrate using water as a dispersion medium, and 19.39 g of water were mixed and stirred for 120 minutes, after which 0.11 g of Surfynol 465 (Nisshin Chemical Industries, Ltd., product name), which is a surface conditioner, was further mixed and stirred for another 15 minutes to obtain a hydrophilic composition. Table 1 shows the content ratio (parts by mass) of each component in the composition. The content ratio (parts by mass) of the inorganic particles and the surface conditioner shown in Table 1 does not include the solvent.
[0093] Example 2 A hydrophilic composition was obtained in the same manner as in Example 1, except that L-7D (product name, manufactured by Mitsubishi Chemical Corporation) was used instead of Surfynol 465, and each component was mixed to obtain the composition (parts by mass) shown in Table 1.
[0094] Example 3 A hydrophilic composition was obtained in the same manner as in Example 1, except that M-7D (product name, manufactured by Mitsubishi Chemical Corporation) was used instead of Surfynol 465, and each component was mixed to obtain the composition (parts by mass) shown in Table 1.
[0095] (Examples 4 to 6) A hydrophilic composition was obtained in the same manner as in Example 1, except that the stirring time was changed from 120 minutes to 240 minutes and the components were mixed so as to obtain the composition (parts by mass) shown in Table 1.
[0096] <Preparation of glass with hydrophilic film> A piece of glass measuring 7.6 cm x 5.2 cm x 1.3 mm thick was washed with isopropyl alcohol. The composition obtained in each example was collected with a dropper, the liquid was dropped onto the edge of the glass, and the composition was applied using a Bemcot (wiping method). The coating was heated at 60°C for 3 minutes to form a hydrophilic film with a thickness of 0.1 μm, and a test sample of glass with a hydrophilic film was obtained.
[0097] The test materials were subjected to the following evaluations. The results are shown in Table 1.
[0098] [Anti-fogging] (Breath test: initial stage) In a laboratory at room temperature of 25°C, breath was blown onto the hydrophilic film from a position 5 cm away, and the presence or absence of fogging was visually confirmed. If no fogging occurred, it was rated as "A", and if fogging occurred, it was rated as "B".
[0099] (Breath test: after heat resistance test) The following heat resistance tests were carried out on the test materials. Heat resistance test: The test material was heated at 130° C. for 5 days under atmospheric pressure using a clean oven (manufactured by Espec Corporation, model: PVHC-231M). After the test, the test material was subjected to a breath test in the same manner as above, and the fogging was evaluated.
[0100] (Breath test: after scratch resistance test) The following scratch resistance test was carried out on the test materials. Scratch resistance test: Steel wool (#0000) was placed on the film, and then a 200 g weight was placed on top of that, and the steel wool with the weight placed on it was moved back and forth 10 times. After the test, the test material was subjected to a breath test in the same manner as above, and the fogging was evaluated.
[0101] [Table 1]
[0102] Details of each component shown in Table 1 are as follows. (Inorganic particles) Alumina A: AS-520-A (manufactured by Nissan Chemical Industries, Ltd., product name, colloidal solution of alumina hydrate with water as the dispersion medium (non-volatile content concentration 20% by mass), particle shape: granular, average particle diameter 15 nm) (Surface conditioner) B1: Surfynol 465 (trade name, manufactured by Nissin Chemical Industry Co., Ltd., acetylene glycol compound, HLB value: 13, non-volatile content concentration 100% by mass) B2: L-7D (manufactured by Mitsubishi Chemical Corporation, product name, polyglycerol laurate, HLB value: 17, non-volatile content 100% by mass) B3: M-7D (manufactured by Mitsubishi Chemical Corporation, product name, polyglycerol myristate ester, HLB value: 16, non-volatile content 100% by mass)
Claims
1. Contains inorganic particles and a surface conditioner, the surface conditioner contains a compound having a hydroxyl group, The hydrophilic composition, wherein the compound has an HLB value of 12 or more and 19 or less.
2. The hydrophilic composition of claim 1 , wherein the compound is a polyglycerol fatty acid ester compound.
3. 3. The hydrophilic composition according to claim 2, wherein the polyglycerol fatty acid ester compound is a compound represented by the following general formula (1): 【Chemistry 1】 [In formula (1), a represents an integer of 1 or more, and R 1 represents a hydrocarbon group having 10 or more carbon atoms.
4. The hydrophilic composition of claim 1 , wherein the compound is an acetylene glycol compound.
5. The hydrophilic composition according to claim 4 , wherein the acetylene glycol compound is a compound represented by the following general formula (2): 【Chemistry 2】 [In formula (2), m and n each independently represent an integer of 0 or more, m+n represents 1 or more, and R 2 , R 3 , R 4 , and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; L 1 , L 2 each independently represents an ethylene group or a propylene group.
6. Contains inorganic particles and a surface conditioner, the surface conditioner contains a compound having a hydroxyl group, The compound has an HLB value of 12 or more and 19 or less.
7. The hydrophilic film according to claim 6 , wherein the compound is a polyglycerin fatty acid ester compound.
8. 8. The hydrophilic film according to claim 7, wherein the polyglycerol fatty acid ester compound is a compound represented by the following general formula (1): 【Chemistry 3】 [In formula (1), a represents an integer of 1 or more, and R 1 represents a hydrocarbon group having 10 or more carbon atoms.
9. The hydrophilic film according to claim 6 , wherein the compound is an acetylene glycol compound.
10. The hydrophilic film according to claim 9 , wherein the acetylene glycol compound is a compound represented by the following general formula (2): 【Chemistry 4】 [In formula (2), m and n each independently represent an integer of 0 or more, m+n represents 1 or more, and R 2 , R 3 , R 4 , and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; L 1 , L 2 each independently represents an ethylene group or a propylene group.
11. An article with a hydrophilic film, comprising the hydrophilic film according to any one of claims 6 to 10.
Citation Information
Patent Citations
Hydrophilic copolymer and hydrophilic composition
JP2023030386A
